Mobile app development with Ionic 2 : cross-platform apps with Ionic, Angular, and Cordova - Griffith, Christopher (O'Reilly Media, 2017)
"Learn how to build app store-ready hybrid apps with the Ionic 2, the framework built on top of Apache Cordova (formerly PhoneGap) and Angular. This practical guide shows you how to use Ionic's tools and services to develop apps with HTML, CSS, and TypeScript, rather than rely on platform-specific solutions found in Android, iOS, and Windows Phone"--